Respuesta :

For this case we must find an expression equivalent to:

[tex](x ^ {\frac {4} {3}} * x ^ {\frac {2} {3}}) ^ {\frac {1} {3}}[/tex]

By definition of power properties we have to:

[tex](a ^ n) ^ m = a ^ {n * m}[/tex]

So, rewriting the expression we have:

[tex]x ^ {\frac {4} {3 * 3}} * x ^ {\frac {2} {3 * 3}} =[/tex]

[tex]x ^ {\frac {4} {9}} * x ^ {\frac {2} {9}} =[/tex]

By definition of multiplication of powers of the same base, we put the same base and add the exponents:

[tex]x ^ {\frac {4} {9} + \frac {2} {9}} =\\x ^ {\frac {4 + 2} {9}} =\\x ^ {\frac {6} {9}} =\\x ^ {\frac {2} {3}}[/tex]

Answer:

Option B

lucic

Answer:

[tex]x^{2/3}[/tex]

Step-by-step explanation:

The question is on rules of rational exponents

Here we apply the formulae for product rule where;

[tex]= a^{n} *a^{t} = a^{n+t} \\\\\\\\=(x^{4/3} *x^{2/3} ) = x^{4/3 + 2/3} = x^{6/3} = x^{2} \\\\\\=(x^2)^{1/3} \\\\\\=\sqrt[3]{x^2}[/tex]

[tex]=x^{2/3}[/tex]